Photocatalytic applications of carbon quantum dots for wastewater treatment - Umi Rabiatul Ramzilah, P. Remli; Azrina, Abd Aziz; Lan, Ching Sim; Minhaj Uddin, Monir; Kah Hon, Leong (Elsevier, 2023)
Photocatalysis process of wastewater that consists of biodegradable pollutants has a significant influence on the ecology system, especially the water resources. Photocatalysis is a harmless process that mineralizes pollutants with the help of highly oxidizing free radicals (•OH and O2•-), thus converting them into carbon dioxide and water, which is nontoxic to the environment. General information on photocatalysis, mechanism of the process, as well as photocatalysts material used in the process were explained in this chapter. Literature on the fundamentals of carbon quantum dots (CQDs) derived from biomass was elaborated. There are various routes to synthesize CQDs that show distinct advantages and disadvantages. Besides, the application of CQDs in photocatalysis was explained in detail. Brief information on the biomass from watermelon rinds as a potential carbon source to synthesize CQDs was enclosed in this literature as well. © 2023 Elsevier Ltd. All rights reserved.